Stability assessment of underground machine hall of Rogun HPP based on the results of physical modeling and in-situ observations - E. Freiberg; A. Kolichko; A. Fedchun; A. Yolkin; I. Grigoriev (The Southern African Institute of Mining and Metallurgy, 2003)
Abstract: The paper describes the engineering-geological conditions and the structural decisions of the underground machine hall of Rogun HPP under construction in Tadjikistan on Vaksh river as well as the results of physical model studies and long-term in-situ investigations of the variation of the stress-strain state of the surrounding rock mass and the supports of openings, and the assessment of the stability of openings during and after the construction. The analysis of the results of long-term in-situ observations and previous model studies permitted to make the assessment of the present-day state of the machine hall and give recommendations of its further use. Zusammenfassung: Im Vortrag werden die ingenieurgeologischen Bedingungen und konstruktiven Lösungen für die unterirdischen Maschinenhalle des in der Republik Tadshikistan am Fluss Wachsch im Bau stehenden Rogunskaja-Wasserkraftwerkes, die Ergebnisse von experimentellen Forschungen (in physikalischen Modellen) und Naturbeobachtungen der Spannungs-Verformungszustandsänderungen des umliegenden Felsmassivs und Ausbaues von Untertagebauten, sowie Ergebnisse der Bewertung der Standfestigkeit von Untertagebauten während des Bauvorganges und nach der Bauperiode beschrieben. Auf Grund der Analyse von Ergebnissen der dauernden Naturbeobachtungen und früher durchgeführten geomechanischen Modellversuche wird der heutige Zustand der Maschinenhalle des Wasserkraftwerkes bestimmt und werden die Empfehlungen für ihren weiteren Benutzung angeführt. Annotation: L’exposé décrit les conditions d’ingénieur et celles géologiques, et les solutions constructives de la salle des machines de la Centrale hydroélectrique (CHE) Rogounskaya sur le fleuve Vakhch, les résultats d’études expérimentales (sur des modèles physiques) et d’observations extérieures sur place concernant des changements de l’état de tension-déformation d’un massif environnant et du cuvelage des excavations, ainsi que les résultats d’évaluation de la stabilité de l’excavation au cours de la construction et à la période post-construction. A la base de l’analyse des résultats des observations de longue durée et des études préalables géomécaniques sur des modèles, l’évaluation de l’état actuel de la salle des machines de la CHE est effectueé, et les recommandations sur son utilisation ultérieure sont présentées.